A scale-free topology model with fault-tolerance and intrusion-tolerance in wireless sensor networks. (November 2016) - Liu, Haoran; Yin, Rongrong; Liu, Bin; Li, Yaqian
Highlights: Two criterions of measuring the topological properties are discussed. Effect of degree distribution on topological properties is analyzed mathematically. The scale-free topology model has adjustable scaling exponent is proposed. The proposed model is robustness to random faults and selective remove attacks. Abstract: The scale-free topology is robust when confronted with random faults, but it is fragile when confronted with selective remove attacks. In this paper, we propose a new scale-free topology model which has both fault-tolerance against random faults and intrusion-tolerance against selective remove attacks at the same time. Then the mathematical expression of the topological degree distribution is derived. Through analyzing the effect of topological degree distribution on these properties of topological fault-tolerance and topological intrusion-tolerance, the optimal scale-free topology which can keep the fault-tolerance and maximize intrusion-tolerance is obtained. We performed extensive experiments on the proposed model and compared it with other existing models. The simulation results show that the new scale-free topology model can keep the character that the scale-free topology has a stronger robustness to random faults. And it also can reduce their fragility for selective remove attacks and further prolong its lifetime. Graphical abstract: The topology structure entropy achieves its maximum when the proper scaling exponent is found.